Dirección: un arte entendido desde la técnica y la filosofía - Garófalo Zambrano, Aurelio Andrés (2018)
In this text you will find a detailed exploration of the narrative elements within the script and the scene, highlighting on the main importance of the actor and his correct communication with the director, an extended investigation about the acting abstract, the definition, understanding and correct application of the method for the creation of an actor-director language.